2021
DOI: 10.1038/s41598-021-91918-5
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced levitation of ultralight carbon aerogels via temperature control

Abstract: We demonstrate that ultralight carbon aerogels with skeletal densities lesser than the air density can levitate in air, based on Archimedes' principle, when heated with light. Porous materials, such as aerogels, facilitate the fabrication of materials with density less than that of air. However, their apparent density increases because of the air inside the materials, and therefore, they cannot levitate in air under normal conditions. Ultralight carbon aerogels, fabricated using carbon nanotubes, have excellen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Micropores of carbon nanofibers and carbon nanotubes had dimensions ranging from 1.8 to 2.0 nm, whereas mesopores and macropores had diameters ranging from 2 to 250 nm. In addition, the specific surface area ranges from 164–186 m 2 /g [ 189 ]. Parameters such as skeletal density, refractive index, and the thermal conductivity of silica aerogels could be determined in silica aerogels.…”
Section: Recent Trends Of Starch As Biopolymermentioning
confidence: 99%
“…Micropores of carbon nanofibers and carbon nanotubes had dimensions ranging from 1.8 to 2.0 nm, whereas mesopores and macropores had diameters ranging from 2 to 250 nm. In addition, the specific surface area ranges from 164–186 m 2 /g [ 189 ]. Parameters such as skeletal density, refractive index, and the thermal conductivity of silica aerogels could be determined in silica aerogels.…”
Section: Recent Trends Of Starch As Biopolymermentioning
confidence: 99%
“…The hierarchical porous framework fabricated by a freeze-drying process using the growth of ice in the dispersion as a template produces ultralight and robust aerogels because it consists of strong SWCNT-CMC composite nanofiber networks. [32,33] The diameter of SWCNT-CMC composite nanofibers is smaller by more than an order of magnitude than that of microfibers fabricated by electrospinning, providing more opportunities for acoustic energy loss within the material. Furthermore, by confirming the consistency with the Biot-Johnson-Champoux-Allard (Biot-JCA) model, [34] which simultaneously considers the air-borne and solid-borne sound in the material, we showed that both the porous structure and elastic modulus of the framework of the ultralight SWCNT aerogel contribute to sound absorption.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Sun et al reported a graphene aerogel with a density of 0.16 mg/cm 3 [ 21 ], which is approximately one sixth of air density and remarkably light. It has also been reported that ultralight aerogels with density less than air density can be levitated in air by controlling the temperature and selectively expanding the air inside the aerogel [ 22 ]. Such ultralight materials with ultimate lightness have the potential for further applications such as in communication and sky transportation [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we manufactured the ultralight materials with a density less than 5 mg/cm 3 by compositing single-walled CNT and sodium carboxymethyl cellulose (CMC) using freeze-drying. Single-walled CNTs facilitate the fabrication of materials in the density range approaching air density due to their high aspect ratio and mechanical properties [ 22 ]. CMC was used as dispersant [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%